Masked Atheism : Catholicism and the Secular Victorian Home - LaMonaca, Maria (Book collections on Project MUSE., 2008)
"Why did the Victorians hate and fear Roman Catholics so much? This question has long preoccupied literary and cultural scholars alike. Masked Atheism: Catholicism and the Secular Victorian Home by Maria LaMonaca begins with the assumption that anti-Catholicism reveals far more about the Victorians than simple theological disagreements or religious prejudice. An analysis of anti-Catholicism exposes a host of anxieties, contradictions, and controversies dividing Great Britain, the world's most powerful nation by the mid-nineteenth century." "LaMonaca situates texts by Charlotte Bronte, George Eliot, Christina Rossetti, Elizabeth Barrett Browning, Michael Field, and others against a rich background of discourses about the growing visibility of Anglo and Roman Catholicism in Victorian England. Masked Atheism will contribute a fresh perspective to an ongoing conversation about the significance of Catholicism in Victorian literature and culture."--Jacket